Measuring Social Influence in Online Social Networks - Focused Literature Review on Human Behaviors - Shyamala N. Chalakudi; Gnana Bharathy; Dildar Hussain; DakshinaMurthy Kolluru (Journal of Applied Marketing Theory)
Measuring an individual's social influence (SI) capability is gaining traction with the rapid growth and expansive reach of online social networks (OSN). However, most existing frameworks and methods are confined to graphical theories or the structural properties of these networks. Even behavioral investigations are often limited to a narrow set of influencing behaviors and confront significant challenges in encompassing the breadth of human psychological characteristics. This study aims to address this gap through an exhaustive and focused literature review, concentrating on the definitions of human behavior characteristics rooted in established sociology and psychology theories. Beyond providing a comprehensive overview, the study identifies twelve key human characteristics essential for measuring SI, craftily grouped into quadrants for practical implementations. Additionally, the research discusses the limitations of current approaches and proposes new primary research avenues for future exploration.